PENGARUH PENAMBAHAN SERBUK DAUN TANAMAN KAYU MANIS (Cinnamomum burmannii) PADA PAKAN TERHADAP PROFIL DARAH (KADAR HEMATOKRIT, KADAR HEMOGLOBIN, TOTAL LEUKOSIT DAN TOTAL ERITROSIT) IKAN NILA (Oreochromis niloticus) YANG DIINFEKSI Streptococcus agalactiae - Sri Lestari; Firma Fika Rahmawati; Rahmad Jumadi (Jurnal Perikanan Pantura (JPP), 2018)
Bacterial disease like Streptococcosis which is caused by Streptoccoccusagalactiae becomesthe most important problem that often arise in the aquaculture business. The disease can be100% cause of death. One of the prevention efforts is using phytopharmaca in cinnamon leaf(Cinnamomunburmanni). This traditional herb is eco-friendly, safe for consumers and it does nothave any residue. Chemical compounds contained in cinnamon leaves have function asantioxidants, to increase metabolism, growth and non-specific immune response in fish. Thisstudy is to determine the effect and find the best dose of the addition of cinnamon leaf powder infood given to Tilapia that infected by Streptococcus agalactaiae. The tested dose is 0%, 0.25%,0.5%, 1%. Observed parameters were blood profile (hematocrit level, hemoglobin level, totalerythrocytes and total leukocytes) and water quality. The results were analyzed by ANOVA usingRAL with 95% credibility level. The results obtained in the study by adding cinnamon leafpowder to the given food to tilapia that was infected by Streptococcus agalactiae affect the bloodprofile (hematocrit level, hemoglobin level, total erythrocytes and total leukocytes). A dose of0.25% is the best dose for hematocrit level, hemogobline level and erythrocytes total. While thedose of 1% is the best dose for the total value of leukocytes. Doses of 0.25% and 1% can beapplied to tilapia culture to prevent Streptococcosis disease caused by Streptococcus agalactiaebacteria.